Geographic variation in diterpene-based secondary metabolites and level of defence in an aposematic nudibranch, Goniobranchus splendidus. (28th December 2018) - Winters, Anne E; White, Andrew M; Cheney, Karen L; Garson, Mary J
Abstract: Nudibranchs are often chemically defended with a variety of secondary metabolites that they obtain from dietary sources or produce de novo . This study details the chemical profile of the nudibranch Goniobranchus splendidus across five sites on the east coast of Australia. This species is especially diverse in secondary metabolites and sequesters a multitude of compounds from a varied sponge diet including spongian diterpenes, rearranged diterpenes and norditerpenes. Goniobranchus splendidus has a colourful body pattern, components of which are used to warn predators of toxins. Therefore, description of metabolite occurrence and quantification within G. splendidus individuals from different regions can help provide a better understanding of how animals obtain chemical defences from their diet and how this influences the evolution of warning signals. We found that populations differed in the abundance, type and richness of secondary metabolites, and that there was high individual variation between specimens from the same population. There was high chemical richness in the mantle rim, which differs from the selective accumulation of compounds in some other nudibranch species. We also found geographic differences in the potency of chemical extracts in model bioassays measuring the anti-feedant effects on Palaemon shrimp and toxicity to brine shrimp. Geographic and individual variation in the richness and abundance of secondary metabolites may have important implications for defence against predation. This study highlights the need to investigate intraspecific variation in secondary metabolites to understand better the nature of complex chemical defences in the marine environment.